Effect of IV alteplase on the ischemic brain lesion at 24–48 hours after ischemic stroke. (27th November 2018) - Mair, Grant; von Kummer, Rüdiger; Morris, Zoe; von Heijne, Anders; Bradey, Nick; Cala, Lesley; Peeters, André; Farrall, Andrew J.; Adami, Alessandro; Potter, Gillian; Sandercock, Peter A.G.; Lindley, Richard I.; et al.
Abstract : Objective: To determine whether alteplase alters the development of ischemic lesions on brain imaging after stroke. Methods: The Third International Stroke Trial (IST-3) was a randomized controlled trial of IV alteplase for ischemic stroke. We assessed CT or brain MRI at baseline (pretreatment) and 24 to 48 hours posttreatment for acute lesion visibility, extent, and swelling, masked to all other data. We analyzed associations between treatment allocation, change in brain tissue appearances between baseline and follow-up imaging, and 6-month functional outcome in IST-3. We performed a meta-analysis of randomized trials of alteplase vs control with pre- and postrandomization imaging. Results: Of 3, 035 patients recruited in IST-3, 2, 916 had baseline and follow-up brain imaging. Progression in either lesion extent or swelling independently predicted poorer 6-month outcome (adjusted odds ratio [OR] = 0.92, 95% confidence interval [CI] 0.88–0.96, p < 0.001; OR = 0.73, 95% CI 0.66–0.79, p < 0.001, respectively). Patients allocated alteplase were less likely than controls to develop increased lesion visibility at follow-up (OR = 0.77, 95% CI 0.67–0.89, p < 0.001), but there was no evidence that alteplase reduced progression of lesion extent or swelling. In meta-analysis of 6 trials including IST-3 (n = 4, 757), allocation to alteplase was associated with a reduction in ischemic lesion extent on follow-up imaging (OR = 0.85, 95% CI 0.76–0.95, p = 0.004). Conclusion: Alteplase was associated with reduced short-term progression in lesion visibility. In meta-analysis, alteplase reduced lesion extent. These findings may indicate that alteplase improves functional outcome by reducing tissue damage. Classification of evidence: This study provides Class II evidence that IV alteplase impedes the progression of ischemic brain lesions on imaging after stroke.